Low and mismatched socioeconomic status between newlyweds increased their risk of depressive symptoms: A multi-center study - Gan, Hong; Li, Mengdie; Wang, Xiaorui; Yang, Qianhui; Tang, Ying; Wang, Baolin; Liu, Kaiyong; Zhu, Peng; Shao, Shanshan; Tao, Fangbiao (Frontiers in Psychiatry, 2023)
Background: There is evidence that low socioeconomic status (SES) increases susceptibility to depression, but few studies have focused on the effect of marital SES matching on depression. This study aimed to explore the impact of SES indicator matching on depressive symptoms in newlyweds and clarify the interaction of depressive symptoms between couples. Methods: We assessed newlyweds’ depressive symptoms (N = 28,179 couples) using the 9-item Patient Health Questionnaire. Logistic regression models and restricted cubic splines were used to explore the association between SES indicator matching and depressive symptoms and the interaction of depressive symptoms in newlyweds, respectively. Results: Compared with newlyweds with both high-level SES, the newlyweds with both low-level SES, male higher SES, or female higher SES had increased risk of depressive symptoms in husbands (OR = 1.31; 1.22; 1.30), wives (OR = 1.30; 1.36; 1.32), and couples (OR = 1.48; 1.56; 1.57) (all P < 0.05). In addition, as the level of depression in one partner increases, the risk of depression in the other partner also increases. Conclusion: Mismatched SES and low-level SES between couples have adverse effects on depressive symptoms in newlyweds, with depressive symptoms having a positive association between newlyweds.